Development of the HOTS Test to Measure Students' Critical Thinking Skills on Optical Instrument Materials - Ernawati, Hakiki; Galib, La Maronta; Anas, Muhammad (Universitas Muhammadiyah Makassar, 2023)
The objective of the study was to: 1) develop and produce a HOTS test that is valid and reliable; 2) examine the quality of the items; and 3) measure the critical thinking skills of high school students on the optical instruments material based on the HOTS test developed. Employing Research and Development (R D) method, this study combined two approach models, namely the Wilson Model and the modified Oriondo and Antonio Model (2014) and the Successive Approximation Model (SAM) by Michael Allen and Richard Sites (2019). This study involved 37 students selected by purposive sampling as test subjects. The results of the study show that: 1) HOTS tests that were valid and reliable, where there were 31 valid questions out of the 60 items tested with a product-moment correlation coefficient of 0.72/high and a test reliability coefficient of 0.79/high; 2) the level of difficulty index of the items is in the range of 0.03-0.92, where 12 items with low discriminating power that need to be revised, while 16 items with very low discriminating power need to be replaced and the effectiveness of the distractor show that there were 13 items with options that need to be replaced; and 3) trials conducted on the HOTS test developed revealed students’ critical thinking skills level, namely 16% low, 65% moderate, and 19% high. Therefore, it can be concluded that the use of the HOTS test is appropriate to measure students’ critical thinking skills.